Photosynthetic response and recovery of Antarctic marine benthic microalgae exposed to elevated irradiances and temperatures - Salleh, S; Andrew McMinn (2011)
Exposure to high temperatures affects the photosynthetic processes in marine benthic microalgae by limiting the transport of electrons, thus reducing the ability of the cell to use light. This causes damage to the Photosystem II (PSII) and may lead to photoinhibition. However, the PSII of benthic microalgal communities from Brown Bay, eastern Antarctica, were relatively unaffected by significant changes in temperature. Benthic microalgae exposed to temperatures up to 8Celsius degree and an irradiance of 450 lmol photons m-2 s-1 did not experience any photosynthetic damage or irreversible photoinhibition. The effective quantum yield (DF/Fm0) at 8Celsius degree (0.433 +- 0.042) was higher by comparison to cell incubated at -0.1 Celsius degree (0.373 +- 0.015) with similar irradiances. Temperatures down to -5 Celsius degree at a similar irradiance showed a decrease in photosynthesis with decreasing temperature, but no severe photoinhibition as the cells were able to dissipate excess energy via non-photochemical quenching and recover from damage. These responses are consistent with those recorded in past studies on Antarctic benthic microalgae and suggest that short-term temperature change (from -5 to 8 Celsius degree) will not do irreversible damage to the PSII and will not affect the photosynthesis of the benthic microalgae.